Elastic–plastic intermittent re-arrangements of frictionless, soft granular matter under very slow isotropic deformations - Luding, Stefan (Frontiers in Physics, 2023)
How do soft granular materials (or dense amorphous systems) respond to externally applied deformations at different rates and for different system sizes? This long-standing question was intensively studied for shear deformations but only more recently for isotropic deformations, like compression–decompression cycles. For moderate strain rates, in the solid-like state, above jamming, the system appears to evolve more or less smoothly in time/strain, whereas for slow enough deformations, the material flips intermittently between the elastic, reversible base state and plastic, dynamic “events.” Only during the latter events, the microstructure re-arranges irreversibly. The reversible base state involves both affine and non-affine deformations, while the events are purely non-affine. The system size and rate dependence of the events are studied, providing reference data for comparison in future studies evaluating materials like hydrogel particles.